10TH GRADE "SOCIO-ECONOMIC GEOGRAPHY OF THE WORLD" COURSE ON THE TOPIC OF GEOGRAPHY OF WORLD TRANSPORT USING THE STRATEGY “GENEALOGY OF DECISIONS” (“DECISION MAKING”) (World Bulletin of Management and Law, 2023)
This article describes the 10th grade “socio-economic geography of the world” Course on the topic of geography of World transport using the strategy “genealogy of decisions” (“decision making”).